(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chronic kidney disease (CKD) patients and their clinicians seek ways to mitigate the risk of CKD progression and its associated complications. Emerging data suggest that dietary modifications may be beneficial adjuvant approaches to reducing the risk of adverse CKD outcomes. This review focuses on several different dietary patterns, including the Dietary Approaches to Stop Hypertension and Mediterranean diets, and their kidney health benefits. We discuss how healthful dietary patterns are lower in dietary acid load and how improving diet quality may slow the progression of CKD. We also discuss some barriers that may impede socially disadvantaged individuals from following healthful diets. Dietary patterns low in dietary acid load might slow the progression of CKD. Current evidence suggests that a reduction in dietary acid load could be beneficial in patients with CKD, but the supremacy of any particular diet is yet to be established. Additional randomized controlled dietary interventions among CKD patients are needed to inform evidence-based recommendations, which can be tailored to an individual’s preferences and ability to access healthful foods.